Financial slack as driver of brazilian firms’ growth - Rezende, José Francisco; Macedo, David Gradvohl (Revista de Administração da UFSM, 2020)
Purpose – To determine the influence of the financial availabilities, as a component of organizational slack, on firms’ growth. Researchers’ discussions concerning organizational slack reveal instances of heterogeneity and divergence in literature on both from theoretical and empirical perspectives. Design/methodology/approach – We developed an embracing theoretical framework drew on confirmatory factor analysis and structural equation modeling techniques, we refined and tested indicators for financial slack. We restored just financial availabilities data about Brazilian corporations listed on the B3 market. Findings – We cannot confirm that all of the states of the financial slack affects organizational growth. Research limitations/implications – We make further research directions to deepen financial slack knowledge on corporate growth. Practical implications – For practitioners, we provide new methodological and indicator directions to scale slack and impact on organizational growth. Originality/value – Research and discussion on organizational choices about generating and taking advantage of slack are essential when considering risk, fund raising and liquidity positions to support organizational growth.